The Influence of halal lifestyle and digital technology on gen Z's decision to use Islamic Banking services - Mingka, Asrawi Fahmi; Syahriza, Rahmi; Syakir, Ahmad (LPMP Imperium, 2024)
The role of financial institutions in developing the community's economy, particularly within the Sharia economy, is continually evolving to address the opportunities and challenges presented by the digital financial era. Financial institutions must strengthen their operations and services to enhance their contributions to the Sharia economy. In this context, students are encouraged to actively save at Islamic banks, as doing so represents an effective approach to financial management. This research employs a quantitative method, utilizing questionnaires distributed to students from the Faculty of Islamic Economics and Business at UINSU for data collection. The results indicate that the trend towards a halal lifestyle, along with advancements in digital technology, significantly influences the decisions of Generation Z students to utilize Islamic banking services. Public interest statements The findings of this study suggest that the growing interest of Generation Z in Islamic banking, driven by their commitment to a halal lifestyle and the influence of digital technology, presents a significant opportunity for the growth of the Islamic economy in Indonesia. Article Info: Received 7/24/2024 | Revised: 9/18/2024 | Accepted: 9/23/2024 | Online First 9/30/2024